Cobalt/Manganese Oxides as Theragnosis Nanoplatforms With Magnetic Resonance/Near-Infrared Imaging for Efficient Photothermal Therapy of Tumors - Liu, Jichun; Wu, Genfa; Tang, Zhiyong; Sun, Qi; Wu, Jianxin; Lv, Renfa (Frontiers in Materials, 2019)
The combination of near-infrared (NIR) response and imaging response is a hot research area in which the function of nanomaterials are maximized. However, such materials reported so far have problems such as complex synthesis. Herein, hydrophilic porous and hollow cobalt/manganese oxide (CMO) nanocrystals (NCs) were successfully prepared via a facile and green hydrothermal route. The CMO NCs show strong near-infrared (NIR) absorption, resulted from the defect structure due to a coexistence of Co2+ and Co3+ in as-prepared CMO NCs. Thus the CMO NCs exhibit an excellent photothermal performance, showing photothermal efficiency up to 43.2%. In addition, the CMO NCs possess the ability for magnetic resonance (MR) imaging with the longitudinal relaxivity (r1) is up to 3.48 mM−1 s−1. Finally, we, for the first time, proved the CMO nanocrystals as a promising photothermal agent. Our work provides the insight of Mn-based control agents and photothermal agents for photothermal theragnosis therapy.